Adubação orgânica e mineral no estabelecimento de mudas clonais de café conilon brs ouro preto na amazônia central - Sprey, Maylla (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
The growth of coffee seedlings is characterized as one of the most important activities in the formation of new coffee crops. The main problem faced by coffee growers is the low fertility of soils in the Amazon. Thus, this work aimed to evaluate the influence of organic and mineral fertilization on the development of seedlings, the availability of nutrients in the soil and on the concentration of nutrients in the leaves in the Conilon coffee clonal seedlings grown in a Yellow Latosol. The study was carried out in a greenhouse with a randomized design, in a factorial desighn (3x8), with three clones of Conilon coffee (C-120; C-125; C-199) and eight formulations of isolated and associated fertilization, evaluate biometric parameters, such as changes in soil fertility and nutrient levels in the leaves of coffee seedlings. The results of the study demonstrated that that clones C-199 and C-120 were superior to C-125 in the variables height and root dry matter. The C-199 presented better levels of N, Mg, Fe and Cu in the leaves. Fertilization with NPK resulted in the smallest diameter for the plants after 180 days, while the chicken + biochar litter promoted an increase in the pH values in H2O and KCl, a reduction in Al3+ and H++Al3+. The combination of chicken litter + biochar + NPK was the best fertilizer for the availability of nutrients in the soil. The N content in the leaf was influenced by its mineral fertilization and the levels of P and K contents in the leaves were higher in the treatment of chicken + biochar + NPK. Biochar was the best fertilizer for the levels of Ca and Mg in the leaves and the treatment without fertilization was better in the contents of Zn and Mn, Cu responded in a variable way in relation to fertilization and clone. It can be concluded that the chicken bed + biochar + NPK promoted improvements in most soil factors and in the development of seedlings, which had a better response in the availability of nutrients in the soil and in the leaf content for Conilon BRS Ouro Preto coffee leaves.
Keywords: Coffea canephora; solos amazônicos; nutrição de plantas